2010
DOI: 10.1371/journal.pntd.0000746
|View full text |Cite
|
Sign up to set email alerts
|

Family Relationship, Water Contact and Occurrence of Buruli Ulcer in Benin

Abstract: Background Mycobacterium ulcerans disease (Buruli ulcer) is the most widespread mycobacterial disease in the world after leprosy and tuberculosis. How M. ulcerans is introduced into the skin of humans remains unclear, but it appears that individuals living in the same environment may have different susceptibilities.ObjectivesThis study aims to determine whether frequent contacts with natural water sources, family relationship or the practice of consanguineous marriages are associated with the occurrence of Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 42 publications
4
45
2
2
Order By: Relevance
“…Therefore, when the population in these African countries can have the access to improved water source, incidences of this disease fall. This phenomenon bolsters the disease transmission model [17] [18] that suggests the pathogen transferred to terrestrial mammal or human acting as hosts for infection spread. "Mysterious disease" Buruli Ulcer thus may spread from biting of such aquatic hemiptera insect (common name Water strider, Gerris sp.…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, when the population in these African countries can have the access to improved water source, incidences of this disease fall. This phenomenon bolsters the disease transmission model [17] [18] that suggests the pathogen transferred to terrestrial mammal or human acting as hosts for infection spread. "Mysterious disease" Buruli Ulcer thus may spread from biting of such aquatic hemiptera insect (common name Water strider, Gerris sp.…”
Section: Resultsmentioning
confidence: 70%
“…A number of case-control studies allowed for the direct identification of potential risk factors for contracting the disease (Table 2). 6,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] A review article evaluating identified risk factors was published in 2010. 88 …”
Section: Risk Factors and Transmissionmentioning
confidence: 99%
“…In accordance with the prevailing assumption that M. ulcerans infection foci are associated with wetlands, most of the case-control studies conducted identified contact with or proximity to water bodies as a risk factor for contracting BU. 6,74,[76][77][78]80,[83][84][85][86][87] Common factors associated with a lower risk for BU reported in several comparative studies were wound care and hygiene 73,76,77,80,83,84 as well as wearing protective clothing. 6,73,76,77,84 In southeastern Australia, exposure to mosquitoes was identified as an additional risk, 73 implicating mosquitoes in the transmission of M. ulcerans in this region.…”
Section: Risk Factors Connected With Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Still others have found that direct contact with aquatic environments is a major risk factor (Aiga et al, 2004;Raghunathan et al, 2005;Debacker et al, 2006;Sopoh et al, 2010), and M. ulcerans has been detected in fish (Eddyani et al, 2004), aquatic snails (Marsollier et al, 2004), aquatic insects (Portaels et al, 1999), and submerged terrestrial plants (McIntosh et al, 2014). While the culturing of M. ulcerans from an aquatic invertebrate (Portaels et al, 2008) suggested a potential reservoir or vector for BU (e.g., Merritt et al, 2010), Benbow et al (2008) discounted predatory aquatic insects as a potential vector because the number of insects and presence of M. ulcerans in these insects are similar at BU-endemic and non-endemic sites.…”
Section: Introductionmentioning
confidence: 99%